Silk Fibroin‐Carbon Nanotube Composite Electrodes for Flexible Biocatalytic Fuel Cells. (30th June 2016) - Tseng, Peter; Perotto, Giovanni; Napier, Bradley; Riahi, Pamela; Li, Wenyi; Shirman, Elijah; Kaplan, David L.; Zenyuk, Iryna V.; Omenetto, Fiorenzo G.
Abstract : Conformal silk/carbon nanotube (CNT)/enzyme composites for fuel cell applications are presented. The films are pliable and wrap around curved surfaces such as a pipette tip, can be cut to assume the shape of an antenna, or can be used in contact with fruit to provide power using the sugars from the nectarine pulp as fuel.